Motivation and The Concept of Self-Regulation: Theory and Implications for English Language Teaching and Learning in Colombia - Beatriz Peña Dix (Voces y Silencios: Revista Latinoamericana de Educación)
Motivation is a complex concept, particularly when applied to the learning of a second or foreign language. For this reason and due to the importance that the notion of motivation has in the field of education, this topic has generated great interest among teachers and researchers in L2, making this one of the central concerns in socio-cognitive motivational approaches.  For this reason, the main aim of this article is to critically examine the theory and the implications of motivation in relation to the concept of self-regulation or autonomy in foreign language teaching and learning. Frequent reference is made to the case of the teaching of English in the Colombian context in order to exemplify some of the definitions and issues related to motivation in the foreign language classroom.